Impacts of Landscape Pattern Changes in Hangzhou Bay Intertidal Wetlands on Regional Nitrogen Removal Under Multiple Stressors - Zhihao Xu; Yangjie Li; Xue Wu; Xin Zhao; Bassem Jalali; Bin Wang; Zhi Yang; Juan Wang; Xin Wang; Cheng He; Hongliang Li; Jianfang Chen (Journal of Marine Science and Engineering, 2026)
Hangzhou Bay has long experienced excessive nitrogen loading coupled with limited hydrodynamic exchange, leading to some of the highest nitrogen concentrations in China’s coastal waters. As critical land-sea ecotones, intertidal wetlands play a crucial role in mitigating nitrogen pollution across the bay. However, rapid urbanization and extensive reclamation since 1990 have led to a loss of over 50% of the intertidal wetlands in southern Hangzhou Bay. In this study we measured sediment denitrification and anammox potentials across key habitats: salt marshes (vegetated by Spartina alterniflora, Phragmites australis, and Scirpus mariqueter), bare mudflats, and shellfish aquaculture zones. We used 15N isotope tracing techniques coupled with slurry incubation experiments. Analysis of sediment physicochemical properties was conducted to elucidate the driving mechanisms of nitrogen removal. By integrating wetland landscape evolution with regional nitrogen budgets, we evaluated the nitrogen sink function of these intertidal wetlands. Our results revealed a distinct spatial hierarchy in denitrification potential, decreasing in the order: S. alterniflora (13.02 ± 3.54 μmol·N·kg−1·h−1) > shellfish aquaculture zones (12.86 ± 7.50 μmol·N·kg−1·h−1) > P. australis (11.54 ± 1.80 μmol·N·kg−1·h−1) > S. mariqueter (7.33 ± 2.08 μmol·N·kg−1·h−1) > bare mudflats (5.99 ± 1.62 μmol·N·kg−1·h−1). S. alterniflora has higher primary productivity, biomass accumulation, and a more robust root system structure. It regulates the content and availability of sediment organic carbon, the supply of nitrate nitrogen, pH, and water content. These regulations subsequently enhance denitrification. In contrast, shellfish aquaculture zones enhance denitrification potential primarily through bioturbation, which increases water content and lowers pH conditions. An integrated assessment of denitrification potential and landscape patterns revealed that, despite ongoing habitat loss, the remaining intertidal wetlands in southern Hangzhou Bay still remove about 30.65% of exogenous inorganic nitrogen. This finding underscores their critical role as effective pollution buffers under high nitrogen loading.